Identifikasi Enterobius vermicularis Pada Spesimen Anal Swab - Nunung Sulistyani (SEHATI: Jurnal Kesehatan, 2026)
Pinworms (Enterobius vermiculari) are intestinal parasitic nematodes in humans. Pinworm infections can affect various age groups, including children. The impacts of Enterobius vermicularis infection in children include malnutrition, low body weight, stunting, and anemia. This study aimed to identify Enterobius vermicularis in anal swab specimens from students in class B1 of Kindergarten KB-TK BAIK Krapyak Panggungharjo Sewon Bantul Yogyakarta. Anal swab specimens were obtained using Scotch tape or cellophane tape. Microscopic examination of the anal swab preparations was performed at 40x objective magnification. Detection of Enterobius vermicularis was indicated by the presence of eggs. Data were analyzed descriptively and presented in narrative form, figures, and tables. The results showed that none of the 10 students who participated in the study had Enterobius vermicularis infection. The conclusion of the study was that Enterobius vermicularis was not identified in the anal swab specimens of students in class B1 of Kindergarten KB-TK BAIK Krapyak Panggungharjo Sewon Bantul Yogyakarta.